2013
DOI: 10.1039/c3tc31423e
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and luminescence properties of green-emitting NaBaScSi2O7:Eu2+phosphors for near-UV-pumped light emitting diodes

Abstract: Green-emitting phosphor Eu 2+ doped NaBaScSi 2 O 7 was synthesized by a solid-state reaction, and the photoluminescence properties were investigated in conjunction with a structural analysis. The crystallographic occupancy of Eu 2+ in the Sc silicate NaBaScSi 2 O 7 matrix was studied based on the Rietveld refinements results and the crystal chemistry rules. The optimum concentration of Eu 2+ in the NaBaScSi 2 O 7 phosphor was about 10 mol%, and the concentration quenching mechanism was verified to be the dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 39 publications
(5 reference statements)
2
71
0
Order By: Relevance
“…As per the estimation done in the literature, these three conditions were calculated based on Eq. (1), respectively35. Compared with the calculated values obtained from Si 4+ sites (1200–1250 nm), it can be concluded that the Sr 2+ sites can act as the favorable cation sites for Ce 3+ ion.…”
Section: Resultsmentioning
confidence: 62%
“…As per the estimation done in the literature, these three conditions were calculated based on Eq. (1), respectively35. Compared with the calculated values obtained from Si 4+ sites (1200–1250 nm), it can be concluded that the Sr 2+ sites can act as the favorable cation sites for Ce 3+ ion.…”
Section: Resultsmentioning
confidence: 62%
“…The phase composition and crystal structures of the prepared KBSS:0.002Eu 2+ sample is verified by XRD and analyzed by the Rietveld refinement as presented in Figure A. Since the KBSS is a new host, the related structural information is deficient, thus, we used the reported crystallographic data of KSrScSi 2 O 7 as the initial structure model . The compound KBSS belong to the family of KMRESi 2 O 7 (M = Ba 2+ , Sr 2+ and RE = Y 3+ , Sc 3+ ), which has a monoclinic structure with the space group of P 2 1 / n .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are very suitable for the basic research and investigate their potential application . Chen et al reported a novel blue‐emitting KSrScSi 2 O 7 :Eu 2+ phosphor with high efficiency and excellent thermal stability, which mainly ascribed to the rigid network with the enriched environments of Sc and weak electron–phonon coupling strength . This result further confirms that Sc silicate would be a suitable phosphor matrix for WLEDs.…”
Section: Introductionmentioning
confidence: 82%
“…36 As shown in Fig. 37 Another Eu 3+ center appeared in heavily Eu-doped CsBaB 3 O 6 should be induced by the possible defects with the increase of Eu 2+ doping in the lattices. In heavily Eu-doped CsBaB 3 O 6,, three Eu 2+ together with one Eu 3+ center can be identified in the lattices.…”
Section: (5) the Luminescence Centers In Glass-ceramicmentioning
confidence: 87%